NARASI MEDIA DAN REPRESENTASI GENDER DALAM PEMBERITAAN INARA RUSLI DI MEDIA ONLINE INDONESIA DENGAN PENDEKATAN SARA MILLS - Mohammad Fikriandi Ramdhansyah; Agus Hamdani; Didin Sahidin (Universitas Muhammadiyah Makassar, 2026)
News coverage regarding Inara Rusli’s nikah siri in Indonesian online media has generated public debate that is not only related to legal and moral aspects, but also touches on the issue of gender representation in media narratives. The media plays an active role in shaping meanings about women through the way events are constructed, the parties given space to speak, and the perspectives prioritized. This study aims to examine how Indonesian online media represent Inara Rusli in reporting on nikah siri and how gender power relations are built through news texts. The approach used is Sara Mills’ critical discourse analysis with a descriptive qualitative method. The research data consist of news texts from CNN Indonesia, Kapanlagi.com, Inilah.com, and Suaramerdeka.com published in January 2026 and discussing claims of nikah siri involving Inara Rusli and Insanul Fahmi. The results show that the media dominantly positions women as objects of discourse who must prove claims and be accountable for their personal relationships in the public sphere. Meanwhile, men and legal counsel are more often placed as subjects who have narrative authority and legal legitimacy. This narrative pattern shows the media’s tendency to reproduce patriarchal values through emphasis on aspects of proof, morality, and legality directed at women. The analysis also finds that the reader’s perspective is directed to doubt women’s narratives, while women’s voices are often mediated or marginalized. The conclusion of this study emphasizes that reporting on Inara Rusli’s nikah siri in Indonesian online media still shows inequality in gender representation and has not fully applied the principles of gender-sensitive journalism.